Producing biofuels in low-income countries: An integrated environmental and economic assessment for Tanzania - Branca, Giacomo; Felix, Erika; Maltsoglou, Irini; Rincón, Luis E.; Thurlow, James (Springer, 2016)
This paper jointly evaluates the greenhouse gas emissions and economic impacts from producing biofuels in Tanzania. Sequentially-linked models capture natural resource constraints; emissions from land use change; economywide growth linkages; and household poverty. Results indicate that there are economic incentives to convert unused lands to sugarcane-ethanol production, but only grasslands (not forests) have a reasonable carbon payback period. There are also strong socioeconomic reasons to involve smallholders in feedstock production in order to reduce rural poverty, especially since our results indicate that biofuels have little effect on food production. Yet smallholders require more land than large-scale plantations and so face more binding natural resource and emissions constraints. Overall, environmental constraints alter the socioeconomically optimal biofuel strategy for Tanzania by limiting potential poverty reduction. Unlike previous studies, our integrated assessment suggests that a mixed farming system with greater emphasis on large-scale plantations is more appropriate for producing sugarcane-ethanol in Tanzania.